2013
DOI: 10.1007/s00362-013-0503-4
|View full text |Cite
|
Sign up to set email alerts
|

A toolbox of permutation tests for structural change

Abstract: The supLM test for structural change is embedded into a permutation test framework for a simple location model. The resulting conditional permutation distribution is compared to the usual (unconditional) asymptotic distribution, showing that the power of the test can be clearly improved in small samples. Furthermore, the permutation test is embedded into a general framework that encompasses tools for binary and multivariate dependent variables as well as model-based permutation testing for structural change. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
4
22
0
Order By: Relevance
“…The parameter instability tests considered have first been suggested in the context of time series regressions but can also be applied to other contexts (e.g., Hjort and Koning, ; Zeileis and Hothorn, ). More specifically, the stability of the regression coefficients is tested, using the sup LM test of Andrews () for numerical partitioning variables:supLM=supi=i̲,,ı¯}{in1in1||Vfalse^1false/2n1false/2:zzfalse(ifalse)xitalicεfalse^22, where z i denotes observation i of the considered partitioning variable, after ordering according to increasing size denoted by z ( i ) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter instability tests considered have first been suggested in the context of time series regressions but can also be applied to other contexts (e.g., Hjort and Koning, ; Zeileis and Hothorn, ). More specifically, the stability of the regression coefficients is tested, using the sup LM test of Andrews () for numerical partitioning variables:supLM=supi=i̲,,ı¯}{in1in1||Vfalse^1false/2n1false/2:zzfalse(ifalse)xitalicεfalse^22, where z i denotes observation i of the considered partitioning variable, after ordering according to increasing size denoted by z ( i ) .…”
Section: Methodsmentioning
confidence: 99%
“…The parameter instability tests considered have first been suggested in the context of time series regressions but can also be applied to other contexts (e.g., Hjort and Koning, 2002;Zeileis and Hothorn, 2013). More specifically, the stability of the regression coefficients is tested, using the supLM test of Andrews (1993) for numerical partitioning variables:…”
Section: Estimation: Model-based Treesmentioning
confidence: 99%
“…According to [12], permutation tests for structural change from the framework of [13] cannot only be derived for the simple location model but for both the nonparametric and parametric (model-based) permutation tests. Literally, they found that exchangeability of the errors might be a too strong assumption in time series applications where the dependence structure of the observations cannot be fully captured within the model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compute the sum of squares residual for the single model and the sub sample as RSST, RSS1 and RSS2.. Calculate the reference value of the F-statistic, F using(12).…”
mentioning
confidence: 99%
“…[25], [22] and [8] and the references given therein. Motivated by these results, we propose the following distribution free procedure to test H 0 : Given the original sample pair x 1 , .…”
Section: Divergence Based Testsmentioning
confidence: 99%